1995
DOI: 10.1016/0009-9236(95)90021-7
|View full text |Cite
|
Sign up to set email alerts
|

Ceftazidime pharmacokinetics in preterm infants: Effects of renal function and gestational age*

Abstract: Dosage recommendations for ceftazidime administration in preterm infants during the first week of life should be based on gestational age and GFR. Additional adjustments in dosage are indicated in preterm infants who are exposed prenatally to indomethacin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 41 publications
(4 reference statements)
1
41
0
Order By: Relevance
“…The ceftazidime/inulin clearance ratio was 0.72 for both groups. Glomerular filtration rates, as measured by inulin clearances, were similar in both groups and were all within the same range reported by us previously (21). Values for total body clearance, apparent volume of distribution, serum elimination half-life, and inulin clearance were not significantly different for both groups.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The ceftazidime/inulin clearance ratio was 0.72 for both groups. Glomerular filtration rates, as measured by inulin clearances, were similar in both groups and were all within the same range reported by us previously (21). Values for total body clearance, apparent volume of distribution, serum elimination half-life, and inulin clearance were not significantly different for both groups.…”
Section: Resultssupporting
confidence: 88%
“…Pharmacokinetic studies are therefore necessary to optimize dosing regimens. We have previously demonstrated that the use of the lowest recommended dose for preterm infants, i.e., 25 mg of ceftazidime per kg given intravenously twice daily, resulted in high concentrations of ceftazidime in serum throughout the entire dosing interval (21). However, serious side effects were not seen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, the comparative PPK analysis described here (11,23), cefazolin (14), cefoperazone (8,38), cefotaxime (21), ceftazidime (40,44), ceftizoxime (26), ceftriaxone (30,32), flucloxacillin (22), meropenem (46), piperacillin (25), and ticarcillin (10) are low (less than 0.4 liters/kg) in adults due to aqueous solubility. (B) Correlation between protein binding ratio and V. The apparent V was strongly associated with the protein binding ratio.…”
Section: Discussionmentioning
confidence: 80%
“…Fourteen antibiotics were reviewed in 16 studies. The values of antibiotic CL from the literature were divided into two groups: circles indicate PCA of Ն33 weeks or BW of Ն2,000 g for amikacin (36), amoxicillin (11,23), aztreonam (13), cefoperazone (38), cefotaxime (21), ceftazidime (40,44), ceftizoxime (26), ceftriaxone (32), meropenem (46), and piperacillin (25); squares indicate PCA of Ͻ33 weeks or BW of Ͻ2,000 for cefoperazone (8), flucloxacillin (10), piperacillin (25), ticarcillin (11), and vancomycin (12). The figure shows that CL is associated with protein binding ratios and that the relationship between renal CL and protein binding is stronger than that between total CL and protein binding.…”
Section: Discussionmentioning
confidence: 99%